Islam and human rights advancing a U.S.-Muslim dialogue - Hunter, Shireen; Malik, Huma ‫ (Significant issues series, 2005)
In the last few years, issues related to human rights, including encouraging the democratization of Muslim societies from the Middle East to Southeast Asia, have acquired great importance in shaping the character of U.S.-Muslim relations and U.S. policy toward Muslim countries. An important impetus behind this development were the tragic events of 9/11, which demonstrated the destructive potential of militant groups that use a distorted interpretation of Islam as justification for their actions. These events also led to a greater realization by the United States--and the West--that a lack of democracy and lack of respect for human rights have been contributory factors to the rise of militant Islam